A vulnerability index formulation for historic facades assessment. (1st April 2023) - Fontenele, Amanda; Campos, Vanessa; Matos, Ana Mafalda; Mesquita, Esequiel
Abstract: The study of historic facades is an essential subject for the valorization and conservation of human cultural identity. The evaluation of the vulnerability of ancient Constructions requires the adoption of a specific and appropriate methodology depending on the purpose and scale of the analysis, demanding the identification of the main constructive aspects and the existing damages. From the literature survey, most of the vulnerability assessment is focused on the behaviour of the building as a whole and vulnerability assessment on dynamic actions. Brazil is the fifth largest country globally and has a wide variety of historical heritage. Thus, this research proposes a new methodology to evaluate the vulnerability of historic facades based on a building sample of the historic centre of Viçosa, Brazil. As vulnerability parameters were considered, the Facade Conservation State, Elements connected to the facade, Facade Geometry, Facade Openings, and Facade Orientation. The hierarchization of each vulnerability parameter was based on the expert's evaluation collected by a questionnaire and the Hierarchical Analytical Process. Results reveal that Facade Conservation State was the main influence parameter (0.80), followed by Facade Openings (0.50) and Facade Orientation (0.50). The proposed model was then validated to a set of 11 historic facades of Viçosa do Ceará. Graphical abstract: Image 1 Highlights: Methodology for assessing the vulnerability of historic facades. Definition of 5 parameters to characterize vulnerability classes of historic facades. Parameters weights estimation based on experts' opinion and Hierarchy Analytical Process. Vulnerability index of historic facades (Vif) obtained from vulnerability classes (Ki) and the vulnerability weights (Wi). Model validation using facades of historic buildings facades of Ceara (Brazil).